PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN STRATEGI IDEAL PROBLEM SOLVING BERMUATAN PENDIDIKAN KARAKTER - Muchayat, - (JPP, 2011)
This research is the development research, done by applying 4-D Thiagarajan model, thathas been modified, by four phases of developing process. They are: defining, planning,developing, and disseminating. One that is developed is learning devices that includessyllabus, lesson plan, student work sheet, student book, and ability problem solving testinstrument. Techniques of data collection in this research by using validation sheetlearning teaching process set, observation of student activity sheet, questionnaire ofmotivates to study sheet, observation teacher capability sheet in learning teachingmanagement and the test of studentÃ¢â¬â¢s ability of problem solving. The result of thisresearch shows that learning devices is valid and effective. The validity and the effectivitylearning devices shown by from result of try out are: studentsÃ¢â¬â¢ ability in problem solvinghas reached the mastery learning, higher than KKM; the average of studentsÃ¢â¬â¢ ability inproblem solving by using learning devices with IDEAL problem solving strategy withcharacter education content is 74,69 is higher than the average of studentsÃ¢â¬â¢ ability inproblem solving using expository with conventional teamwork that is only 70,75; thestudentsÃ¢â¬â¢ activity and studying motivation in the learning process influence positively tothe studentsÃ¢â¬â¢ ability problem solving. The character education content that is observed isgood category in observation of student activity.Keywords: Character Education, Development, Problem Solving